Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1515/cclm-2016-0575
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs in lipoprotein and lipid metabolism: from biological function to clinical application

Abstract: microRNAs (miRNAs) are short (~ 22 nucleotides), non-coding, single-stranded RNA molecules that regulate the expression of target genes by partial sequencespecific base-pairing to the targeted mRNA 3′UTR, blocking its translation, and promoting its degradation or its sequestration into processing bodies. miRNAs are important regulators of several physiological processes including developmental and metabolic functions, but their concentration in circulation has also been reported to be altered in many pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 193 publications
0
32
0
Order By: Relevance
“…They regulate gene expression by binding to the 3’-untranslated regions (3’-UTR) of mRNAs, leading to the degradation or translation repression of the targeted mRNAs [8890]. miRNAs have been identified and demonstrated to regulate nearly all cellular processes, i.e., cell cycle, apoptosis, autophagy, differentiation and metabolism [9193]. The role of miRNAs in lipid metabolism has been extensively reviewed [9296].…”
Section: Regulation Of Scap/srebps By Micro-rnamentioning
confidence: 99%
“…They regulate gene expression by binding to the 3’-untranslated regions (3’-UTR) of mRNAs, leading to the degradation or translation repression of the targeted mRNAs [8890]. miRNAs have been identified and demonstrated to regulate nearly all cellular processes, i.e., cell cycle, apoptosis, autophagy, differentiation and metabolism [9193]. The role of miRNAs in lipid metabolism has been extensively reviewed [9296].…”
Section: Regulation Of Scap/srebps By Micro-rnamentioning
confidence: 99%
“…Moreover, recent studies indicated that microRNAs (miRNAs) emerge as novel biomarkers and potential therapeutic targets in the treatment of hyperlipidemia and hepatic lipid dysregulation [11]. MiRNAs, which are small noncoding RNAs molecules composed of 19-25 nucleotides, have been implicated in the regulation of a wide spectrum of biological processes through binding to the 3 0 UTR of target genes and further inducing mRNA destabilization and/or translational repression [12].…”
Section: Introductionmentioning
confidence: 99%
“…Over recent decades, miRNAs have been proposed as central regulators of lipid and lipoprotein metabolism [43][44][45]. The miR-33 family has attracted attention because of its role in the regulation of genes involved in HDL metabolism, cholesterol efflux, fatty acid oxidation, and bile acid synthesis and secretion [46].…”
Section: Discussionmentioning
confidence: 99%